Global Disk Oscillation Modes in Cataclysmic Variables and Other Newtonian Accretors - Ortega Rodríguez, Manuel (2007)
Diskoseismology, the theoretical study of small adiabatic hydrodynamical global perturbations of geometrically thin, optically thick accretion disks around black holes (and other compact objects), is a potentially powerful probe of the gravitational field. For instance, the frequencies of the normal mode oscillations can be used to determine the elusive angular momentum parameter of the black hole. The general formalism developed by diskoseismologists for relativistic sys- tems can be readily applied to the Newtonian case of cataclysmic variables (CVs). Some of these systems (e.g., the dwarf nova SS Cygni) show rapid oscillations in the UV with periods of tens of seconds and high coherence. In this paper, we assess the possibility that these dwarf nova oscillations (DNOs) are diskoseismic modes. Besides its importance in investigating the physical origin of DNOs, the present work could help us to answer the following question. To what extent are the similarities in the oscillation phenomenology of CVs and X-ray binaries (XRBs) indicative of a common physical mechanism?